Quantum Size Effect on Band Gap and Effective Mass of ZnS Nano-Particle - Kavosh Tehrani, M.; Babazadeh, A. (Asian Journal of Chemistry, 2010)
In this paper, we calculate the band gap of ZnS nanoparticle and show that it increases with decreasing its size. The simplest way for discussing this phenomenon and finding the band gap for different sizes is to use effective mass approximation. We show this method isn't useful for smaller sizes than 2.5 Å because the effective mass of particles below 2.5 Å also depends on the size. The density functional theory was used to obtain the band gap of ZnS nanoparticle. This theory also be used for determine the effective mass for various particle size. We find equation that shown variation effective mass for various particle sizes of ZnS. This equation fit with experimental results.